Detection of contamination of sunflower seed coats with Verticillium dahliae - ZHANG Gui; ZHANG Yuanyuan; TIAN Yongwei; ZHAO Xiaojun; ZHANG Guang; ZHOU Hongyou; JING Lan; ZHAO Jun (浙江大学学报. 农业与生命科学版)
Sunflower Verticillium Wilt is a soil-borne disease caused by Verticillium dahliae, which can infect a variety of crops, resulting in a serious decline in both yield and quality. The conidia and microsclerotia in sunflower debris are the principal sources of infection. A nested polymerase chain reaction (PCR) was used to detect the contamination of V. dahliae in sunflower seed coats. Seven sunflower varieties were selected to isolate DNA from their seed coats, and then performed a nested PCR by using specific primers of V. dahliae and the universal primers of fungi (ITS1/ITS4). The PCR products were sequenced then BLAST-searched in GenBank. In order to confirm the PCR results, green fluorescent protein (GFP) labeled V. dahliae was used to inoculate sunflower roots. The seed coats were then removed from inoculated sunflower seeds and detected GFP signal under a fluorescence microscope. The results showed that all the amplified PCR bands belonged to V. dahliae isolated from the seed coats of the tested sunflower cultivars. Meanwhile, variable seed contamination ratios were found among different sunflower varieties. The lowest and highest contamination ratios were observed in 3638C (10.0%) and Chi029X115R (25.0%) varieties, respectively. Moreover, the GFP signals obtained on the seed coats of inoculated sunflowers further supported the PCR results. Based on the above results, we confirm that the sunflower seed coat is an important tissue for V. dahliae colonization, and it is the main carrier for the long distance transmission of the sunflower Verticillium Wilt. Additionally, we conclude that the nested PCR method is fast and highly reliable to detect V. dahliae contamination in sunflower seed coats.